Dora the explorer : Dora's Halloween [videorecording (DVD)] - Gifford, Chris; Walsh, Valerie; Weiner, Eric; Herles, Kathleen, 1991-; Chad, Harrison (Paramount Pictures, 2009)
Dora and Boots share a Halloween filled with adventure, including a spooky journey where they encounter Little Monster, take a wild broomstick ride, and try to find their way out of a pumpkin patch. Includes Dora's Halloween Hunt Game, and Nick Jr. Baby video sneak peek.